Practitioner perspectives and assumptions about the role media plays in communication strategies that aim to change the behaviour of an individual - Erfani-Ghadimi, Nooshin (My University, 2016)
The aim of this research is to investigate practitioner perspectives and assumptions about the role media plays in communication strategies that aim to change the behaviour of an individual. It assesses whether these assumptions are consistent with the way the media is actually used in the campaigns of three organisations, and then asks whether there is any correlation between the apparent effectiveness of the campaign and the assumptions of media effect held by practitioners. The purpose is to gain better insight, from a media practitioner’s perspective, into how communication practitioners working on public campaigns understand the impact of the media. Three case studies are analysed, focusing on the use of print, broadcast and the internet to communicate the key messages in the campaigns. The case studies are of highly visible national organizations, each using the media in a particular way, with varying results. The first case study is of SANRAL's E-tag campaign, a campaign which has struggled to achieve widespread public support for e-tolls in Gauteng; the second, Play4Life, is a campaign launched by loveLife, which has in the past been controversial in its use of mass media, and the last, PhuzaWize, is campaign run by Soul City, generally credited with having an evidence-based and strategic approach to its communication strategies. The research found that the communication strategies used in the campaigns are in line with the compliance gaining, the two-step and multi-step, and with communication for social change models, respectively. Practitioners interviewed for this study however showed slightly differing views on the impact of media. Some seemed to understand the mass media through theoretical prisms described in Hovland’s “magic keys” (of attention, compliance and acceptance), whilst others argued that the messaging must change internal psychological makeup of the audience – as described in De Fleur’s psychodynamic model. Whilst one practitioner was an advocate of educational-entertainment and communication for social development approaches, others made repeated references to the power of inter-personal interactions, which are most in line with Lazarsfeld’s two-step and multi-step models.
A dissertation submitted to the School of Literature, Language and Media, University of the Witwatersrand in fulfilment of the requirements for the degree of Master of Arts by dissertation. 14 March 2016
Keywords: Mass media--Influence; Mass media--Social aspects; Public opinion; Communication--Social aspects